Improving Student Learning Outcomes Through Stem-Based Magic Box Medium in The Concept of Addition Theory - Twiningsih, Anik Twin (International Journal of Research in STEM Education, 2020)
The objective of the study is to determine the improvement of student learning outcomes through the media Magic Box (Magic Box) Based on STEM (Science, Technology, Engineering, Mathematics) on the concept of addition. The subject of the research was class I students in one of the Public Schools in Surakarta City Semester I of 2018/2019 Academic Year as many as 24 students, consisting of 7 male students and 17 female students. The method of the study was Classroom Action Research (CAR) with patterns: planning, implementing, observing, reflecting, and revising. The data were collected by using discussion, observation, tests, field notes, and documentation. Based on the results of the study, it was found that student learning outcomes had increased from cycle I to cycle II. The cycle I was 70.83%, and cycle II was 91.66%. The conclusion of the study is by using instructional media teaching aids Magic Box (Magic Box) Based on STEM (Science, Technology, Engineering, Mathematics) on the concept of addition theory can improve student learning outcomes in first-grade elementary schools in Surakarta City Semester I in the Academic Year of 2018/2019.